English Teachers Classroom Assessment Practices - Saefurrohman Saefurrohman; Elvira S. Balinas (Institute of Advanced Engineering and Science, 2016)
The new language assessment policies in the Philippines and in Indonesia have impact on English teachers’ assessment practices. Classroom assessment; as mandated in the current curriculum of both countries swifts from sources of information to the inseparable process of teaching and learning. This study describes Filipino and Indonesian high school English teachers’ classroom assessment practices in ELL classes.This study was conducted using a mix method design with 48 Filipino and Indonesian junior high school English teachers as respondents who completed the questionnaire on classroom assessment practices. Twelve respondents participated in an interview and observation to further clarify their practices on classroom assessment. The study found that both Filipino and Indonesian junior high school English teachers used assessment for learning as the main purpose of assessment. The majority of Filipino Junior High school English teachers prepared and made their own assessment, while Indonesian junior high school English teachers used items from published textbooks as their primary sources for constructing assessment items. Both Filipino and Indonesian junior high school English teachers used written comments as their primary method for providing feedback. Total score test and a letter grade were the highest percentage methods for providing a final report for both Filipino and Indonesian junior high school English teachers.